2019
DOI: 10.37134/jictie.vol6.5.2019
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality for the Disabled: Review Articles

Abstract: Augmented Reality or "AR" has been recognized for its significant importance in different areas of technology, not to mention its significant presence in the education sector. This research aimed to map the relevant literature on AR usage with the aim of rehabilitating people with disabilities. The search was performed on three databases: Science Direct, IEEE Explore and Web of Science from 2013 to 2018. . Based on our inclusion and exclusion criteria, (n=13) articles were selected. Seven of the studies (n=7/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Our review of the current research on the application of AR in special education showed the potential benefits of AR for individuals with disabilities, including support with self-determination and self-management, guidance through self-instruction in complex tasks resolution, or guidance and location in various environments (Gómez-Puerta, Chiner, Melero-Pérez, & Lorenzo, 2019). Moreover, it may be beneficial to adopt AR technology to allow individuals with mental and physical disabilities to live normally and exercise their hobbies (Alshafeey, Lakulu, Chyad, Abdullah, & Salem, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the current research on the application of AR in special education showed the potential benefits of AR for individuals with disabilities, including support with self-determination and self-management, guidance through self-instruction in complex tasks resolution, or guidance and location in various environments (Gómez-Puerta, Chiner, Melero-Pérez, & Lorenzo, 2019). Moreover, it may be beneficial to adopt AR technology to allow individuals with mental and physical disabilities to live normally and exercise their hobbies (Alshafeey, Lakulu, Chyad, Abdullah, & Salem, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, Baragash, Al-Samarraie, Alzahrani, and Alfarraj (2019) conducted a meta-analysis that eventually supported the effectiveness of AR technology in learning promotion and in obtaining social, living and physical skills among students with special needs. Also, Gomez-Puetra, Chiner, Melero-Perez, & Lorenzo (2019) and Alshafeey et al (2019) illustrated potential advantages of AR for individuals suffering from disabilities and these were self-determination, selfmanagement, guidance, and the promotion of mental and physical disabilities normal living and hobbies. Based on literature dedicated to AR teaching material, positive contributions are provided to the motivation level of students.…”
Section: Discussionmentioning
confidence: 99%
“…Each research provides a broad understanding of the educational benefits that AR technology may offer in those fields of use. However, the study of AR technology in mathematics education is still on the surface (Alshafeey et al, 2019;Lainufar et al, 2021). There is little recent systematic review which provides detailed relevant work of literature in AR's effectiveness and implementations in mathematics education.…”
Section: Introductionmentioning
confidence: 99%